Microstructural characteristics, porosity and strength development in ceramic-laterized concrete - Awoyera, P.O.; Akinmusuru, J.O.; Dawson, Andrew; Ndambuki, J.M.; Thom, N.H. (Elsevier, 2018)
Interfacial bonding between constituent materials and pore sizes in a concrete matrix are major contributors to enhancing the strength of concrete. In a bid to examine how this phenomenon affects a laterized concrete, this study explored the relationship between the morphological changes, porosity, phase change, compressive, and split tensile strength development in a ceramic-laterized concrete. Varying proportions of ceramic aggregates, sorted from construction and demolition wastes, and lateritic soil were used as substitutes for natural aggregates. Strength properties of the concrete specimens were evaluated after 7, 14, 28 and 91 days curing, but morphological features, using secondary electron mode, were examined only at 7 and 28 days on cured specimens, using Scanning electron microscope (SEM). From all the mixes, selected samples with higher 28 day crushing strength, and the reference mix, were further characterized with more advanced analysis techniques, using the mercury intrusion porosimetry (MIP), thermogravimetric analysis (TGA), X-ray Diffractometer, and SEM (backscatter electron mode-for assessment of the interfacial transition properties between aggregates and paste). The reference mix yielded higher mechanical properties than the concrete containing secondary aggregates, this was traced to be as a result of higher peaks of hydration minerals of the concrete, coupled with its low tortuosity and compactness. However, a laterized concrete mix containing both 90% of ceramic fine and 10% of laterite as fine aggregate provided the optimal strength out of all the modified mixes. Although, the strength reduction was about 9% when compared with the reference case, however, this reduction in strength is acceptable, and does not compromise the use of these alternative aggregates in structural concrete.